Environmetrics and receptor modelling of river water quality status at Linggi River Basin, Malaysia - Abdul Zali, Munirah (2013)
Intensifying demands on water resource management have produced many outstanding methods in order to protect our valuable nature. Therefore, in order to conserve the river basin, pollution sources must be tracked attentively owing to land-used and water level variations (low, normal and high). Currently the increasing development trends along Linggi River Basin have pose alarming environmental issues especially on the water resources. In fact, great environmental protection must be established for the surface river water due to its important as a source of drinking water purposes in Negeri Sembilan. Foremost water research in multivariate and modelling techniques lead to combination of cluster analysis (CA), discriminant analysis (DA), principal component analysis (PCA) and receptor modelling to investigate the surface water quality at Linggi River Basin (LRB), Malaysia ranging from year 2000 to 2010. Under cluster analysis three regions were acquired such as high pollution status (HPS), moderate pollution status (MPS) and low pollution status (LPS). Based on thirty water quality parameters only fifteen variables were successfully discriminated as significant water quality parameters in the differentiation of regions and water level classification. Spatial assessment of DA revealed significant anthropogenic influences and seasonal changes at the three regions with DO as the most significant parameter; whereas oil waste and contaminated metals exhibits distinctive features during low, normal and high water level. PCA revealed that only nine river pollution sources (water hardness-natural mineral salt, surface runoff, anthropogenic input, raw sewage disposal, chemical changes, industrial activities, agricultural runoff, rubber effluent and domestic waste) were characterized. Despite that distinguishing the contamination in LRB were identified to be contributed by waste oil, traffic runoff and waste water in temporal assessment via PCA. Source apportionment results concluded that anthropogenic input was the major pollution sources at three cluster regions. However based on temporal variation, waste water, fertilizer waste, and soil runoff also show impacts on the river water quality status suggest the hydrological features and runoff from river play a major role in assimilating and carrying the pollutants during tidal changes. Therefore, this study is expected to support the local environmental agencies in managing the river basin based on the comprehensive and reliable informative results as regards to the spatial and temporal dissimilarity as well as definite pollution sources in Linggi River.